Nonlinear Integer Programming and Global Optimization (Journal of Computational Mathematics, 1999)
Various approaches have been developed for solving a variety of continuousglobal optimization problems. But up to now, less work has been devoted to solvingnonlinear integer programming problems due to the inherent difficulty. This paper manages to transform the general nonlinear integer programming problem into an \"equivalent\" special continuous global minimization problem. Thus any effective global optimization algorithm can be used to solve nonlinear integer programming problems. This result will also promote the research on global optimization. We present an interval Branch-and-Bound algorithm. Numerical experiments show that this approach is efficient. \u00a0
Keywords: Integer programming; Global minimization problem; Branch-bound algorithm.